2008
DOI: 10.1038/sj.bjc.6604444
|View full text |Cite
|
Sign up to set email alerts
|

Sequential induction chemotherapy followed by radical chemo-radiation in the treatment of locoregionally advanced head-and-neck cancer

Abstract: We describe a retrospective series of patients with advanced head-and-neck cancer who were treated with induction chemotherapy followed by radical chemo-radiation. Patients treated with two cycles of induction chemotherapy followed by definitive chemoradiation for squamous cell carcinoma of the head-and-neck region, from 2001 -2006 at the Royal Marsden Hospital, formed the basis of this study. Cisplatin (75 mg m À2 ) on day 1 and 5-FU (1000 mg m À2 ) day 1 -4 was the standard regimen used for induction treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 18 publications
(25 reference statements)
2
31
1
Order By: Relevance
“…Two cycles (every 21 days) of cisplatin (75 mg/m 2 ) on day 1 and 5-fluorouracil (1,000 mg/m 2 ) on days 1 to 4 was the standard regimen used for induction chemotherapy (10). Cisplatin (100 mg/m 2 ) on days 1 and 29 was used for concomitant treatment.…”
Section: Chemotherapymentioning
confidence: 99%
“…Two cycles (every 21 days) of cisplatin (75 mg/m 2 ) on day 1 and 5-fluorouracil (1,000 mg/m 2 ) on days 1 to 4 was the standard regimen used for induction chemotherapy (10). Cisplatin (100 mg/m 2 ) on days 1 and 29 was used for concomitant treatment.…”
Section: Chemotherapymentioning
confidence: 99%
“…stroke). Patients were treated with 65 Gy in 30 fractions to planning target volume 1 (PTV 1) (primary tumour and involved nodes) and 54 Gy to the elective neck (PTV 2), as previously described [13]. Patients diagnosed with unknown primary disease received 60 Gy to the operated neck and 54 Gy to the entire mucosal tube and contralateral neck.…”
Section: Participantsmentioning
confidence: 99%
“…Previously reported studies have shown comparable two years rates for OS (61-66%), LRC (71-76%) and DMFS (79-91%) [25][26][27]. However, these studies had larger inclusion criteria such as inclusion of nasopharynx, inclusion of T1N2 or T3N1 patients whereas our study only had one patient with stage III disease, and all others with T4 or N3 disease.…”
Section: Discussionmentioning
confidence: 42%